Programming the Global Brain. (Communications of the ACM, 2012)
The article focuses on the concept of a global brain and on how programming it differs from traditional computer programming. It describes the global brain as large-scale interconnected human-computer networks and suggests that citizen science, open idea ecologies and data mining are aspects of the global brain. It talks about the diversity of user motivations, error types, and cognition and comments on the creation of social operating systems that would manage both computer and human resources.